Effect of Storage Temperature on Beauveria bassiana (Bals.) Vuill. Viability on Several Carriers - Sri Sukamto (Indonesian Coffee and Cocoa Research Institute, 2006)
One of the entomopatogenous fungus types commonly observed and showed potency as myco-insectiside is Beauveria bassiana(Bals.) Vuill.In order to support effectiveness and patogenous activity of B. bassiana, it is necessary to add a carrying agent that protects its spores from ultra violet ray. This study aims to investigate the effect of storage temperature on viability of B. Bassianaspores on the carrier material. The observation was carried out in the Laboratory of Plant Diseases, Indonesian Coffee and Cocoa Research Institute. The research was arranged in completely randomized design by three factors. The first factor was carrier (C), that consists of C1 = rice flour, C2 = maize flour and C3 = tapioca flour. The second factor was dosage (D), that consists of D1 = 1 g B. bassiana+ 1 g carrier; D2 = 1 g B. bassiana+ 5 g carrier and D3 = 1 g B. bassiana+ 10 g carrier. The third factor was temperature of the storage (T),that consists of T1 = 5oC; T2 = 23oC and T3 = 29oC. Viability of B. Bassiana spores was examined by observing development of 100 blastopores randomly and determined under light microscope with 400 times magnification. Observation was conducted in two replicates after the spores of B. bassiana were kept in the storage for 2, 4, 8 and 16 weeks. The result showed that by adding 1 g tapioca flour and temperature of storage of 5oC was potentiall in keeping viability of B. bassianaspores at least for 2 months. It was due to that tapioca flour gave better effect than rice and maize flours in keeping the storage and appropriate low temperature. Viability of B. bassianaspores decreased with increasing carrier dosage, temperature and duration of the storage. Whereas, storage at 5oC was found to be a better condition in keeping viability of dry pure B. bassianaspores longer than conditions of 23o and 29oC. Key word:Beauveria bassiana, temperature, viability,carrier.